THE INFLUENCE OF DIGITAL LIBRARY SERVICE QUALITY ON STUDENT SATISFACTION - Siregar, Nurul Zahara; Syam, Abdi Mubarak; Hasibuan, Azrai (PERSPEKTIF: Journal of Social and Library Science, 2024)
This research was conducted with the aim of knowing the effect of digital service quality on student satisfaction at the State Islamic University of North Sumatra. This research is a quantitative research. Data collection techniques used in the form of a questionnaire / questionnaire. The selected sample is 100 respondents based on the slovin formula. The method used is a survey research method using a quantitative data analysis approach. The data analysis technique used is data quality test, classic assumption test, and hypothesis test. The results showed that the results of the T test obtained t-count > t-table or (2.327 > 1.660) and the value of Sig. (0.000 <0.05). This shows that there is a positive and significant influence on the quality of digital library services on the level of student satisfaction and the R Square value is 0.52, which means 52% that the magnitude of the influence of digital library service quality on student satisfaction at the State Islamic University of North Sumatra is 52%.